Isolation of a pigment-producing bacterium chryseobacterium sp. from the tentacle of holothuria (lessonothuria) pardalis (Selenka 1867) from Pulau Tinggi, Johor - Siti Najihah Solehin, Siti Najihah Solehin; Nor Shahida Ab Rahman, Nor Shahida Ab Rahman; Muhammad Abdul Latiff Abu Bakar, Muhammad Abdul Latiff Abu Bakar; Aisyah Mohamed Rehan, Aisyah Mohamed Rehan; Kamarul Rahim Kamarudin, Kamarul Rahim Kamarudin
Chryseobacterium sp, a bacteria producing pigment was isolated from the tentacles of Holothuria (Lessonothuria) pardalis (Selenka 1867) from Pulau Tinggi, Johor. This study aimed to observe and genetically identified the presence of bacteria focusing on pigmentproducing bacteria. Thus, the partial 16S ribosomal RNA gene sequence of bacteria obtained and the shape, number of bacteria and gram staining observed using a digital compound microscope. Six gene sequence successfully obtained and the Basic Local Alignment Search Tool (BLAST) analysis suggested three species of bacteria identified from genus Pseudomonas, Chryseobacterium and Klebsiella. Besides, the neighbourhood-joining and Maximum Likelihood method had been used in the phylogenetic analysis to support the identification of bacteria species. The visible spectra of Chryseobacterium sp. were recorded between 400nm to 600nm which is a visible spectrum for carotenoid; orange pigment. However, further analysis is needed to confirm the characterisation and the potential of this pigment in industrial